Leaf Extract of Kentut (Paederia foetida L.) as a Preventive Measure Against Interleukin-6 Expression in the Liver of Mice in a Sepsis Model Injected with Escherichia coli - Savitri, Lisa; Freitas, Maria Do Carmo Da Costa; Kasimo, Elfred Rinaldo; Krissanjaya, Rochmad; Juwita, Syntia Tanu (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Kentut leaves (Paederia foetida L.) are a medicinal plant that can be used as a preventative medicine against sepsis. This plant contains secondary metabolite compounds such as alkaloids, flavonoids, triterpenoids, saponins, and other active compounds. This research aims to to determine the influence and effective dosage of Kentut leaf extract as a preventive measure against IL-6 expression in the livers of mice in a sepsis model injected with E. coli. The method used was a Completely Randomized Design (CRD). The study involved 24 white male mice divided into 6 groups. Data analysis was performed using One way ANOVA. The average values of IL-6 expression in the mouse livers for each group are as follows: KN at 7.09%±0.06; K+ at 26.36%±0.02; K- at 72.60%±0.05; PI (100mg/kgBW) at 71.04%±0.04; PII (300mg/kgBW) at 62.22%±0.02; and PIII (500mg/kgBW) at 40.92%±0.01. The research results indicate an influence of kentut leaf extract as a preventive measure against IL-6 expression in the livers of mice in the sepsis model injected with E. coli, with a significance value of 0.000 or p-value < 0.005. The effective dosage of kentut leaf extract as a preventive measure against IL-6 expression is the PIII dosage of 500mg/kg BW. The anti-inflammatory mechanism in sepsis is thought to be caused by the presence of flavonoids, alkaloids, phenolic acids, and terpenoid compounds. The most likely anti-inflammatory mechanism is believed to involve flavonoids inhibiting cyclooxygenase (COX) and lipoxygenase (LOX) enzymes involved in the synthesis of inflammatory mediators such as prostaglandins and leukotrienes, which can trigger IL-6 production.